Complexity and modification of the bull sperm glycocalyx during epididymal maturation - Sečová, Petra; Hackerová, Lenka; Horovská, Ľubica; Michalková, Katarína; Jankovičová, Jana; Postlerová, Pavla; Antalíková, Jana (The FASEB journal, 2024)
Mammalian spermatozoa have a surface covered with glycocalyx, consisting of heterogeneous glycoproteins and glycolipids. This complexity arises from diverse monosaccharides, distinct linkages, various isomeric glycans, branching levels, and saccharide sequences. The glycocalyx is synthesized by spermatozoa developing in the testis, and its subsequent alterations during their transit through the epididymis are a critical process for the sperm acquisition of fertilizing ability. In this study, we performed detailed analysis of the glycocalyx on the sperm surface of bull spermatozoa in relation to individual parts of the epididymis using a wide range (24) of lectins with specific carbohydrate binding preferences. Fluorescence analysis of intact sperm isolated from the bull epididymides was complemented by Western blot detection of protein extracts from the sperm plasma membrane fractions. Our experimental results revealed predominant sequential modification of bull sperm glycans with N-acetyllactosamine (LacNAc), followed by subsequent sialylation and fucosylation in a highly specific manner. Additionally, variations in the lectin detection on the sperm surface may indicate the acquisition or release of glycans or glycoproteins. Our study is the first to provide a complex analysis of the bull sperm glycocalyx modification during epididymal maturation.
Keywords: Glycoproteins; mužské pohlaví; epididymis; glykokalyx; zvířata; lektiny; polysacharidy; glykoproteiny; Glycocalyx; Spermatozoa; Lectins; skot; Polysaccharides; Epididymis; spermie; Male; Cattle; Animals